2019
DOI: 10.1039/c8nr09434a
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-enabled switch-like paracetamol electrochemical sensor based on thermosensitive polymer and MWCNTs-GQDs composite nanomaterial

Abstract: The reversible and temperature-controlled electrochemical response of the thermosensitive polymer PS-PNIPAm-PS/MWCNTs-GQDs/GCE to paracetamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…PNIPAM features a near body lower critical solution temperature (LCST = 32°C) and biocompatibility, and is thus very appealing for biomedical applications. [32][33][34][35][36] So far the reports mentioning both PVDF and PNIPAM only describe polymer blends for the preparation of electrospun fibers or flat membranes, or the grafting of PNIPAM on PVDF membranes. 37 To date, the preparation of PNIPAM-b-PVDF block copolymers (BCPs) and the study of their self-assembly in selective solvents have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…PNIPAM features a near body lower critical solution temperature (LCST = 32°C) and biocompatibility, and is thus very appealing for biomedical applications. [32][33][34][35][36] So far the reports mentioning both PVDF and PNIPAM only describe polymer blends for the preparation of electrospun fibers or flat membranes, or the grafting of PNIPAM on PVDF membranes. 37 To date, the preparation of PNIPAM-b-PVDF block copolymers (BCPs) and the study of their self-assembly in selective solvents have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the internal resistance of modified-SWNT films, arising from the physical contact between components and the electron transfer resistance between the active materials and the substrate, could reflect the adhesion and π-π stacking system between copolymers and the nanotube [32][33][34]. Therefore, electrochemical impedance spectroscopy (EIS) measurements were performed from 10 5 Hz to 0.01 Hz.…”
Section: Mechanismmentioning
confidence: 99%
“…In recent years, biomolecular computing, as a significant branch of unconventional operations, has been responsible for numerous scientific developments and breakthroughs [1][2][3][4]. Of these, logic computing devices constructed by the integration of biocatalytic reaction and stimuli-responsive film electrode have shown enormous potential in some fields, such as biosensing [5][6][7], information transmission [8,9], medical diagnostics [10,11], and drug delivery [12]. However, these logic devices reported were often simple in operation and unable to simulate complex environments.…”
Section: Introductionmentioning
confidence: 99%